(untitled) (El Taco en la Brea, 2018)
This work aims to return, anachronistic (Didi-Huberman) and rhapsodically (Antelo 2013), to a set of Brazilian experiences in which we can read different images of literature and Latin American arts whose singularity and potency should be interrogated. This mandate at the same time critical and ethical, follow de routes that Brazil has occupied in the construction of the field of Latin American literature and in the image of Latin America. Therefore, we propose focalize in figures that since 1492 at present appear insistently in literature and in the other Latin American arts, stirring their imaginary powers. I refer to sirens, cannibals, the primitive, the crazy, the organic and the magical. This figures and paradigmatic elements highlight the relationship between Brazil and the image of Latin America.